A rule made to be broken: on Zarlino, Vicentino, Willaert and parallel congruent imperfect consonances. (16th April 2014) - McKinney, Timothy R.
Abstract: The voice-leading rule of music theory that forbids consecutive perfect consonances of the same size between a pair of voices became firmly entrenched in the 14th century when counterpoint treatises began to replace those describing the older practices of organum and discant. A similar yet far more unusual rule discouraging consecutive imperfect consonances of the same size and quality appeared in the middle of the 16th century in the writings of a small group of music theorists that included two of the most significant of the period, Nicola Vicentino (1555) and Gioseffo Zarlino (1558). Others mentioning the rule about the same time include Jerome Cardan ( c .1546) and Juan Bermudo (1555). Although Vicentino and Zarlino attempted to justify the new rule, their arguments appear strained and lack widespread substantiation in contemporaneous compositional practice. The present study examines their theoretical underpinnings for the rule, agrees with Karol Berger's suggestion that the rule was taught by composer Adrian Willaert, and supports this hypothesis through analysis of Willaert's madrigals. In Willaert's magnum opus, Musica nova, written by early in the 1540s yet not officially published until 1559, parallel imperfect consonances are not avoided in general, but the false relation produced by consecutive major 3rds over a whole-step in the bass sometimes is used for expressive purposes. The fact that Willaert follows the rule less closely in his earlier madrigals than in his mature ones also suggests that it may have been of his own devising rather than being something he himself was taught.